2011
DOI: 10.3414/me10-01-0045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Malocclusion and Heart Rate Variability Indices in Young Adults

Abstract: The data showed an association between malocclusion and lower HRV. Based on our results, orthodontic treatment might contribute not only to improvement of oral esthetic and functional problems but also to improvement of stress and HRV indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We also carried out HRV analysis and compared the ratio of LF/HF, an index of the sympathetic nervous activity [25], nHF, an index of the parasympathetic nervous activity, and SDNN, which is a measure of total autonomic instability [24,25,60], at 1 day before (baseline) and at 1, 7 and 14 days after BO treatment. The LF/HF ratio was significantly increased and nHF was significantly decreased, compared to the baseline at all time points after BO, as expected, because occlusal disharmony increases stress in humans [61,62] and in rats [6]. However, mean HR was unexpectedly reduced in BO mice, compared to the control baseline.…”
Section: Discussionsupporting
confidence: 79%
“…We also carried out HRV analysis and compared the ratio of LF/HF, an index of the sympathetic nervous activity [25], nHF, an index of the parasympathetic nervous activity, and SDNN, which is a measure of total autonomic instability [24,25,60], at 1 day before (baseline) and at 1, 7 and 14 days after BO treatment. The LF/HF ratio was significantly increased and nHF was significantly decreased, compared to the baseline at all time points after BO, as expected, because occlusal disharmony increases stress in humans [61,62] and in rats [6]. However, mean HR was unexpectedly reduced in BO mice, compared to the control baseline.…”
Section: Discussionsupporting
confidence: 79%
“…The HRV indices have been investigated to understand various conditions, including coronary artery disease, heart failure, hypertension, diabetes, chronic obstructive pulmonary disease, renal failure, epilepsy, depression, among others [4,5,10]. In dentistry, HRV has been associated with malocclusion [10], temporomandibular joint dysfunction [11], in dental surgery [12] and effects of sedatives [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, HRV has been associated with malocclusion [10], temporomandibular joint dysfunction [11], in dental surgery [12] and effects of sedatives [13,14]. Ekuni et al [10] evaluated the effects of malocclusion on the HRV indices. The authors found that malocclusion causes chronic stress that can affect the HRV indices.…”
Section: Discussionmentioning
confidence: 99%
“…PRV was measured using a sphygmograph (TAS9 Pulse Analyzer Plus, YKC, Tokyo, Japan) for 15 min at 27 °C with subjects in the supine position and wearing light clothing. The frequency domain information was automatically analyzed with a fast Fourier transform [ 24 , 25 ]. This analysis involved 1000 samples, a 300-ms pulse interval resampling frequency, and a Hanning window function.…”
Section: Methodsmentioning
confidence: 99%